Penerapan Pembelajaran Berbasis Kontekstual dengan "Snack Market Challenge" untuk Meningkatkan Hasil Belajar - Ucik Fitri Handayani; Mochammad Bahtiar Arif (JURNAL ARMADA PENDIDIKAN, 2025)
The main problem in this study was the difficulty students had in forming mathematical models from real situations and manipulating concepts, as well as the passive nature of conventional learning methods. This study aimed to improve the mathematics learning outcomes of grade VIIIA students at Donomulyo Islamic Junior High School in the subject of Two-Variable Linear Equation Systems (SPLDV), which had previously been low. A two-cycle Classroom Action Research (CAR) was conducted on 29 students in class VIIIA at SMP Islam Donomulyo. Cycle I applied an expository method, resulting in an average score of 56.65 with a completion rate of 58.63%. In Cycle II, contextual learning was applied through the “Snack Market Challenge” and balanced group division. The results showed an increase in the average score to 80.65 with a completion rate of 100%, as well as an increase in student enthusiasm and activity. This study recommends the use of contextual learning and educational games to improve student learning outcomes and motivation.